Circulating levels of TNF receptor II are prognostic for patients with peripheral T-cell non-Hodgkin lymphoma. - Heemann, C.; Kreuz, M.; Stoller, I.; Schoof, N.; von Bonin, F.; Ziepert, M.; Loffler, M.; Jung, W.; Pfreundschuh, M.; Trumper, L.; Kube, D. (Clin Cancer Res, 2012)
PURPOSE: Peripheral T-cell non-Hodgkin lymphomas (T-NHL) represent a small but heterogeneous and clinically aggressive subset of NHLs with a poor outcome. Cytokines or their receptors might be associated with the clinical outcome of these lymphomas. Therefore, we tested whether gene variations and serum levels of soluble TNF receptor (TNFR)I (sTNFRI), sTNFRII, interleukin (IL)-10, or sIL-4R are predictive for treatment response in T-NHLs. EXPERIMENTAL DESIGN: Peripheral blood DNA from 117 patients with T-NHL treated in prospective clinical trials was subjected to genotyping analysis. Whenever possible, pretreatment sera were obtained, and circulating levels of sTNFRI, sTNFRII, IL-10, and sIL-4R were determined with a specific capture enzyme-linked immunoassay. RESULTS: Patients characterized by TNFRI-609GG (rs4149570) showed a trend toward better event free survival [EFS; univariate: P = 0.041; multivariate: HR, 1.76; confidence interval (CI), 0.99-3.14 with P = 0.056]. A protective role of IL-10-1087A, -824T, and -597A reported in another study was not confirmed in our cohort. Patients with circulating levels of soluble TNFRII >/=2.16 ng/mL had a 2.07-fold increased relative risk for shorter overall survival (OS; univariate: P = 0.0034; multivariate: HR, 2.07; CI, 0.92-4.70 with P = 0.081) and a 2.49-fold higher risk for shorter EFS (univariate: P = 0.00068; multivariate: HR, 2.49; CI, 1.22-5.08 with P = 0.012). Elevations of circulating levels of sTNFRI, IL-10, and sIL-4R are frequent, but the clinical response in these patients is not significantly different. CONCLUSIONS: Our findings suggest a critical role for TNF-TNFR signaling for the clinical outcome of patients with peripheral T-NHLs.
Keywords: Adolescent; Adult; Aged; Biomarkers, Tumor/*blood; Disease-Free Survival; Female; Gene Frequency; Humans; Interleukin-10/genetics; Kaplan-Meier Estimate; Lymphoma, T-Cell, Peripheral/*blood/diagnosis/genetics/mortality; Male; Middle Aged; Multivariate Analysis; Polymorphism, Single Nucleotide; Prognosis; Receptors, Tumor Necrosis Factor, Type I/genetics; Receptors, Tumor Necrosis Factor, Type II/*blood/genetics; Risk; Young Adult